Pathological Targets for Treating Temporal Lobe Epilepsy: Discoveries From Microscale to Macroscale - You, Jing; Huang, Haiyan; Chan, Clement T. Y.; Li, Lin (Frontiers in Neurology, 2022)
Temporal lobe epilepsy (TLE) is one of the most common and severe types of epilepsy, characterized by intractable, recurrent, and pharmacoresistant seizures. Histopathology of TLE is mostly investigated through observing hippocampal sclerosis (HS) in adults, which provides a robust means to analyze the related histopathological lesions. However, most pathological processes underlying the formation of these lesions remain elusive, as they are difficult to detect and observe. In recent years, significant efforts have been put in elucidating the pathophysiological pathways contributing to TLE epileptogenesis. In this review, we aimed to address the new and unrecognized neuropathological discoveries within the last 5 years, focusing on gene expression (miRNA and DNA methylation), neuronal peptides (neuropeptide Y), cellular metabolism (mitochondria and ion transport), cellular structure (microtubule and extracellular matrix), and tissue-level abnormalities (enlarged amygdala). Herein, we describe a range of biochemical mechanisms and their implication for epileptogenesis. Furthermore, we discuss their potential role as a target for TLE prevention and treatment. This review article summarizes the latest neuropathological discoveries at the molecular, cellular, and tissue levels involving both animal and patient studies, aiming to explore epileptogenesis and highlight new potential targets in the diagnosis and treatment of TLE.